On Thermal-Pulse-Driven Plasma Flows in Coronal Funnels as Observed by the Hinode/EUV Imaging Spectrometer (EIS) - Srivastava, A.K.; Konkol, P.; Murawski, K.; and et. al. (Kluwer Academic Publishers, 2014)
Using one-arcsecond-slit-scan observations from the Hinode/EUV Imaging Spectrometer (EIS) on 5 February 2007, we find the plasma outflows in the open and expanding coronal funnels at the eastern boundary of AR 10940. The Doppler-velocity map of Fe XII 195.120 Å shows the diffuse closed-loop system to be mostly red-shifted. The open arches (funnels) at the eastern boundary of AR exhibit blue-shifts with a maximum speed of about 10 – 15 km s-1. This implies outflowing plasma through these magnetic structures. In support of these observations, we perform a 2D numerical simulation of the expanding coronal funnels by solving the set of ideal MHD equations in appropriate VAL-III C initial temperature conditions using the FLASH code. We implement a rarefied and hotter region at the footpoint of the model funnel, which results in the evolution of slow plasma perturbations propagating outward in the form of plasma flows. We conclude that the heating, which may result from magnetic reconnection, can trigger the observed plasma outflows in such coronal funnels. This can transport mass into the higher corona, giving rise to the formation of the nascent solar wind.
Keywords: Corona; Magnetic fields; MHD; Waves